One-Dimensional Simulation For Single Cylinder Diesel Engine Operating With Ethanol - R., Mamat (2010)

(untitled)
This study intended to perform the one-dimensional simulation for single cylinder diesel engine. The one-dimensional numerical analysis of GT-Power software is used to simulate the commercial single cylinder diesel engine. The diesel engine is simulated to study the characteristic of engine performance when the engine is operating with alcohol as alternative fuel. The simulation results were compared with the data from the diesel engine operating with conventional diesel. It is found that the performance of diesel engine operating with alcohol (ethanol) demonstrate lower engine performance and engine efficiency. The simulations are conducted at full load condition for the engine operating with ethanol and conventional diesel. The simulation results show that the brake power and brake torque reduced maximum of 38.84% and 37.67% respectively for the engine operating with ethanol as compared to conventional diesel. Nowadays, the ethanol is able to compete with standard diesel and the economics have become much more favourable in it production. The decrease of low heating value resulted to increase brake specific fuel consumption and reduces the brake thermal efficiency of engine performance at full load.